Strip AIDS USA : a collection of cartoon art to benefit people with Aids - Robbins, Trina; Sienkiewicz, Bill; Triptow, Robert (San Francisco : Ron Turner, 1988)
Fonds Suzan Daniel (FSD)
Engels
Brochure
Keywords: stripverhalen; aids; Verenigde Staten